PENGARUH PERBEDAAN JENIS PELARUT TERHADAP KADAR FLAVONOID TOTAL BATANG KECOMBRANG (Etlingera elatior) - Adini, Syilvi; Yusransyah; Syilvi Adini; Sofi Nurmay Stiani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Kecombrang stem (Etlingera elatior) contains flavonoid compounds and can be used as a medicine, an antibacterial, and an antioxidant. Several factors influence the extraction compounds in plants, one of which is the type of solvent. This study aimed to determine the effect of different solvents on the total flavonoid content in kecombrang stems. Kecombrang stems were extracted using methanol, 70% ethanol, and 96% ethanol. Qualitative flavonoid analysis was carried out using color reagents and thin-layer chromatography (TLC), and quantitative analysis was carried out using a UV-Vis spectrophotometer. The results of the qualitative flavonoid test showed that all kecombrang stem extracts were positive for flavonoids, indicated by a color change to yellow-orange, and the TLC results showed that all extracts were positive for flavonoids, indicated by light blue fluorescence under UV light 366 nm, with an Rf value range of 0.62-0.66. The results of determining total flavonoid levels in methanol extract were 12.14 mgQE/g, 70% ethanol was 13.55 mgQE/g, and 96% ethanol was 21.77 mgQE/g. One-way ANOVA statistical analysis showed that differences in solvent types significantly affected the total flavonoid levels of kecombrang stems, with a p value <0.05. The highest flavonoid levels in kecombrang stems were found in 96% ethanol extract.